Ugi multicomponent reaction to prepare peptide–peptoid hybrid structures with diverse chemical functionalities. Issue 4 (5th January 2018) - Hartweg, Manuel; Edwards-Gayle, Charlotte J. C.; Radvar, Elham; Collis, Dominic; Reza, Mehedi; Kaupp, Michael; Steinkoenig, Jan; Ruokolainen, Janne; Rambo, Robert; Barner-Kowollik, Christopher; Hamley, Ian W.; Azevedo, Helena S.; et al.
Abstract : Sequence defined peptide–peptoid hybrids create new opportunities for self-assembled nano-structures. Abstract : Monodisperse sequenced peptides and peptoids present unique nano-structures based on their self-assembled secondary and tertiary structures. However, the generation of peptide and peptoid hybrid oligomers in a sequence-defined manner via Ugi multicomponent reaction has not yet been studied. Herein, we report a synthetic strategy that enables both the modification of peptides as well as the generation of sequence-defined peptide–peptoid hybrid structures. Our synthetic methodology rests on the fusion of solid phase peptide synthesis with Ugi multicomponent reactions. We evidence that a diversity of chemical functionalities can be inserted into peptides or used in the design of peptide–peptoid hybrids exploiting a wide functional array including amines, carboxylic acids, hydrocarbons, carbohydrates as well as polymers, introducing a sequence-defined synthetic platform technology for precision peptoid hybrids.